Five Phase Impedance Source VSI with the Capability of Delivering two Loads - Siva V.; Raghuram M.; Singh A.; Singh S.K. (My University, 2025)
The main aim of this paper is to develop a new switching strategy to deliver power to two independent three phase loads operating at different frequencies. In this proposed topology, switched boost and quasi switched boost impedance networks are integrated with five phase inverter to improve the voltage gain profile at two independent loads operation. The shoot through period is inserted in the space vector pulse width modulation technique to implement the proposed strategies. Proposed topologies achieve high voltage gain and control two loads independently without disturbing the conventional inverter operation. In addition, the proposed topologies achieve a wide voltage gain range by controlling the shoot through period and modulation indexes. The Proposed converters are simulated in MATLAB to support the theoretical analysis. Simulation results show the effectiveness of the topologies. © 2023 IEEE.